Pengaruh Kemandirian Belajar Dan Kemampuan AwalTerhadap Berpikir Kritis Pada Mata Kuliah AkuntansiPerusahaan Jasa Pada Mahasiswa Program StudiPendidikan Akuntansi Universitas MuhammadiyahSurakarta Angkatan 2015 - Tri Prasetyowati, Dian; Narimo,MM.,M.Pd,, Dr. Sabar Narimo,MM.,M.Pd (2016)
Education, University of Muhammadiyah Surakarta, April, 2016. This study aims to determine: 1) Effect of independent learning to think critically; 2) Effect of initial ability to think critically; 3) Effect of early learning independence and ability to think critically. This research is a quantitative research associative. This study took place in the Campus of the Faculty of Teacher Training and Education Program Accounting Education Muhammadiyah University of Surakarta. The population in this study were all students of the Faculty of Teaching and Education of Accounting Studies Program University of Muhammadiyah Surakarta Force in 2015, amounting to 240 students. Samples taken as many as 142 students by insidental sampling technique. The data collection technique using the technique of test, questionnaire and documentation. Data analysis technique used is multiple linear regression analysis, t-test, F, R2 test, the relative contribution and effective contribution. The regression results obtained by the regression equation Y = 52.628 + 0.097 X2 + 0,261X1. It is concluded that: 1) Independence learn positive and significant effect on critical thinking. Based on t test obtained t> t table is 3.761> 1.977 and the significance probability value <0.05, namely 0.000. 2) The ability of the initial positive and significant effect on critical thinking. Based on t test obtained t> t table is 4.143> 1.977 and significance probability value <0.05, namely 0.000. 3) Independence of early learning and the ability jointly positive and significant effect on critical thinking. Based on F test obtained F count> Ftable is 23.661> 3.061 and the significance probability value <0.05, namely 0.000. 4) Variable independent learning contribute relative 46,4% and then Variable initial capability provides relative contribution of 53.6%. 5) Variable independent learning contribute effectively 11.8%. Variable initial capability provides effective contribution of 13.6%, bringing the total effective contribution of both variables by 25.4%, while the remaining 74.6% is influenced by other variables not examined.